Meaningfulness as a driver for employee engagement CSR perspective in a multinational company - Suominen, Laura (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Employee engagement is found to be evidently important for international companies to maintain competitive advantage. To engage employee’s companies should fulfil employees’ need for meaningfulness in their work, one way to increase meaningfulness is to engage employees to CSR activities. By combining the concepts of CSR, meaningfulness and employee engagement, this research has set out to understand how to add employee engagement with meaningful CSR. This study was constructed as a single case study in a multinational company. Primary empirical data was gathered by interviewing seven employees of the case company with previous experience on CSR. In addition to these semi-structured interviews data was gathered from secondary sources using the case company’s CSR reports, website and results from an employee engagement survey. The main findings of this research point that employees understand CSR as actions that have a positive impact on society and for them CSR is linked to moral values. CSR can create experience of meaningfulness in and at work, when it is perceived as meaningful. Additionally, meaningful CSR was found to engage employees and employees were found to engage in CSR. These same employees used expressions as ‘pride’, ‘willingness to go the extra mile’ and ‘additional satisfaction’ to describe their feelings towards the company or CSR action. Furthermore, it was identified that the employees who find CSR meaningful and engage to it push the case company to take further CSR actions. Ultimately the research findings concluded that the case company is able to add employee engagement with meaningful CSR. The findings identified different actions that the case company can take to further enhance employee engagement with meaningful CSR. These actions are: increasing CSR communication; taking a ‘glocal’ approach on CSR; involving and empowering employees on CSR matters.